Reading and Writing Skills of Deaf Pupils with Cochlear Implants. (2nd April 2016) - Mayer, Connie; Watson, Linda; Archbold, Sue; Ng, Zheng Yen; Mulla, Imran
Abstract: Thirty-three young people with cochlear implants, aged between 9 and 16 years, were assessed for use of their implant system, cognitive abilities, vocabulary, reading, and writing skills. The group came from throughout England and included 26 born deaf, six deafened by meningitis, one with auditory neuropathy, and five with additional needs. Nineteen had bilateral implants with a mean age at first implantation of three years six months. The majority were educated in mainstream, with 85 per cent using oral communication in school. The group was cognitively able, all scoring within or above the normal range. In terms of receptive and expressive vocabulary, 75 per cent and 67 per cent scored within the average range respectively. Using the Single Word Reading Test, 55 per cent were within the average range, and 21 per cent above. As measured by the York Assessment of Reading Comprehension, 72 per cent were commensurate with hearing peers, and 9 per cent above on reading rate, and 75 per cent within the average range, and 13 per cent above on comprehension. Free writing samples indicated that 25 per cent were performing at the expected level for their age, 19 per cent above, and 56 per cent below. Influences on outcomes were age at implantation, bilateral implantation, and age at testing. Overall this group demonstrated good use of their technology, and much stronger outcomes in vocabulary and reading than evidenced in the deaf population prior to implantation. Writing outcomes were not as strong as in reading, but were not showing the use of non-standard English as in the past, and were showing writing strategies such as invented spelling, common in hearing children.